1999
DOI: 10.1053/euhj.1998.1311
|View full text |Cite
|
Sign up to set email alerts
|

Effects of KATPchannel blockade by glibenclamide on the warm-up phenomenon

Abstract: AimsThe increased tolerance to myocardial ischaemia observed during the second of two sequential exercise tests, i.e. the warm-up phenomenon, has been proposed as a clinical model of ischaemic preconditioning. As ATPsensitive K + channels appear to be a mediator of ischaemic preconditioning in both experimental and clinical studies, the aim of this study was to investigate the role of K ATP channels in the warm-up phenomenon. Methods and ResultsTwenty-six patients with coronary artery disease were randomized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0
5

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 21 publications
2
32
0
5
Order By: Relevance
“…In fact, bamiphylline, a selective antagonist of A 1 adenosine receptors, at a dose previously shown to block adaptation to ischemia during coronary angioplasty, 20 failed to prevent the warm-up phenomenon. 31 The involvement of K ATP channels in the warm-up phenomenon is uncertain. In fact, K ATP channel blockade by glibenclamide, given in the attempt to prevent the warm-up phenomenon at a dose previously shown to block adaptation to ischemia during coronary angioplasty, 18 has yielded conflicting results.…”
Section: Mechanisms Of Ischemic Preconditioningmentioning
confidence: 99%
“…In fact, bamiphylline, a selective antagonist of A 1 adenosine receptors, at a dose previously shown to block adaptation to ischemia during coronary angioplasty, 20 failed to prevent the warm-up phenomenon. 31 The involvement of K ATP channels in the warm-up phenomenon is uncertain. In fact, K ATP channel blockade by glibenclamide, given in the attempt to prevent the warm-up phenomenon at a dose previously shown to block adaptation to ischemia during coronary angioplasty, 18 has yielded conflicting results.…”
Section: Mechanisms Of Ischemic Preconditioningmentioning
confidence: 99%
“…Although many authors consider that improvement of T-1.0 mm in the second test is an expression of IPC [13][14][15][16]19,20,21,31 , the minimum improvement difference is yet to be defined.…”
Section: Discussionmentioning
confidence: 99%
“…By blocking K-ATP channels of beta-pancreatic cells, sulfonylureas and glinides can also act in myocardial K-ATP channels suppressing IPC 3,[13][14][15][16][17][18] . For suppressing this phenomenon of myocardial protection, the repaglinide action is assumed as deleterious, with a potential harmful effect on the myocardium in face of ischemic events.…”
Section: Figure 1 -Correlation Analysis Between the T-10 MM (Index Omentioning
confidence: 99%
See 1 more Smart Citation
“…Glibenclamide has been shown to affect ischaemic preconditioning but trials have not shown beyond doubt that it is associated with increased myocardial infarction. However drugs that inhibit the K ATP channel opening, such as glibenclamide, are related to loss of ischaemic preconditioning [79][80][81] . GLP-1 receptors are found in the heart.…”
mentioning
confidence: 99%